2019
DOI: 10.1590/1807-1929/agriambi.v23n2p90-96
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gas changes of melon seedlings submitted to water salinity

Abstract: The melon is an outstanding fruit crop in Brazil, mainly in the Northeast region due to favorable conditions for cultivation. Water salinity affects the growth and production of several species, but there is tolerance among cultivars of the same species. The objective of this study was to evaluate the growth and gas exchange in melon seedlings subjected to water salinity. Experiment was carried out in a greenhouse belonging to the Center of Sciences and Agri-Food Technology, Federal University of Campina Grand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
(14 reference statements)
0
1
0
1
Order By: Relevance
“…As for the isolated applications of the regulators (0/100% and 100/0% CPPU/IAA, respectively), it was observed that CPPU promoted higher yields for plants under high EC compared to IAA. One of the signs of stress caused by the excess of salts is the rapid and intense reduction in the growth rate, mainly in leaf area, a response caused by the change in physiological parameters (SOUSA et al, 2019). For TDM, a similar behavior was found between the treatments 25/75, 50/50 and 75/25% when the plants were irrigated with normal water, while at a salinity level of 2.0 dS m -1 , they obtained greater accumulated mass (14.32 g) with the proportion 25/75% (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…As for the isolated applications of the regulators (0/100% and 100/0% CPPU/IAA, respectively), it was observed that CPPU promoted higher yields for plants under high EC compared to IAA. One of the signs of stress caused by the excess of salts is the rapid and intense reduction in the growth rate, mainly in leaf area, a response caused by the change in physiological parameters (SOUSA et al, 2019). For TDM, a similar behavior was found between the treatments 25/75, 50/50 and 75/25% when the plants were irrigated with normal water, while at a salinity level of 2.0 dS m -1 , they obtained greater accumulated mass (14.32 g) with the proportion 25/75% (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…) também foi constatada porSousa et al (2019) no crescimento inicial de meloeiro, ao estudar seis cultivares: Natal, Iracema, Goldex, Solares, Mandacaru e Amarelo Ouro, em que a cultivar Natal revelou-se a mais tolerante e Amarelo Ouro mais sensível à salinidade da água na fase inicial de crescimento.A inoculação com os Trichodermas spp. interferiu na tolerância das cultivares (Figura 3E) com mais expressividade nas cultivares Fair Fax e Crimson Sweet em que a aplicação com Trichoderma longibrachiatum proporcionou acúmulo de biomassa em torno de 72,3% e 75,5% contra 60,5 e 57,4% com Trichoderma harzianum, equivalente ao incremento de 16% e 24%, respectivamente, nessas cultivares.…”
unclassified